Desde una reunión científica a la publicación de unos avances delas ciencias biológicas en el Perú - Romero, Leonardo (2006)
This issue is the culmination of a series of events that began at the XV Scientific Meeting organized by the Antonio Raimondi Institute of Biological Sciences (ICBAR), and which took place from August 7 to 9 2006. The Scientific Meetings have been happening year after year since 1991, on the one hand with the desire to show the research carried out by the ICBAR, and on the other to highlight their importance both within our university community, and outside, in the life sciences research community. This work reports and describes the main events that took place at the XV Scientific Meeting and that made this special issue possible.